Endothelial Dysfunction - Old Concepts and New Challenges 2018
DOI: 10.5772/intechopen.76745
|View full text |Cite
|
Sign up to set email alerts
|

Hox Genes in Adult Tissues and Their Role in Endothelial Cell Differentiation and Angiogenesis

Abstract: HOX genes belong to a family of transcription factors characterized by a 183 bp DNA sequence called homeobox, which code for a 61-amino-acid domain defined as the homeodomain. These genes play a central role during embryonic development by controlling body organization, organogenesis, and stem cell differentiation. They can also play a role in adult processes such as embryo implantation, hematopoiesis, and endothelial differentiation. Since endothelial cell differentiation is one of the main steps to initiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…These results also matched with the study done by Bruhl et al (32) , Nova-Lampeti et al (33) , who reported that HOXA9 regulates angiogenesis and stimulate endothelial cell migration and documented that HOXA9 has a precise role in migration of endothelial cells without affecting other processes such as cell cycle/division.…”
Section: Discussionsupporting
confidence: 91%
“…These results also matched with the study done by Bruhl et al (32) , Nova-Lampeti et al (33) , who reported that HOXA9 regulates angiogenesis and stimulate endothelial cell migration and documented that HOXA9 has a precise role in migration of endothelial cells without affecting other processes such as cell cycle/division.…”
Section: Discussionsupporting
confidence: 91%
“…The upregulated genes were involved in functional categories related to the type I interferon (IFN) signaling pathway, virus response, ATP response, purine nucleoside metabolism, and negative regulation of cell proliferation. Among these, we identified CTBP2 , MXI1 , CLMN , IFIT3 , IFITM1 , PTEN , PTK2B , SSTR5 , SPRY1 , and the known factors implicated in VEGF pathways, such as LEPR ( 87 ), HIF3A (GO identifier, 0001944), PTEN ( 88 ), LRG1 ( 82 ), MDK ( 89 ) (GO identifier, 0001944), and HOXA1 ( 90 ). On the other hand, downregulated genes were centered on categories related to cell adhesion, circadian rhythm, extracellular matrix (ECM) organization, negative regulation of DNA binding transcription factor activity, negative regulation of blood coagulation, and response to cyclic AMP (cAMP).…”
Section: Resultsmentioning
confidence: 99%
“…Homeobox proteins encode transcription factors controlling embryonic development, and regulate the proliferation and differentiation of cells throughout the reproductive cycle. It has also been stated that they play critical roles in the growth and development of the endometrium together with estrogen and progesterone hormones that regulate endometrial physiology (26).…”
Section: Discussionmentioning
confidence: 99%